Identification of the Subsurface Structure of Geothermal Working Area of the Hamiding Mountain, North Maluku through Land Surface Temperature (LST) Data and Forward Modeling with the Gravity Method - Muhammad Nafian; Belista Gunawan; Nanda Ridki Permana; Rofiqul Umam (Journal of Natural Sciences and Mathematics Research, 2022)
The Mount Hamiding area has one of the largest geothermal potentials in Indonesia to be exploited. Therefore, this research was conducted with the aim of knowing the subsurface structure in the area using the gravity method. To correlate gravity data in order to obtain parameters to measure the increase in surface temperature using supporting data is land surface temperature. Derivative analysis and 2D modeling carried out by forward modeling is one method that can strengthen the geothermal potential in the area. Based on the Land Surface Temperature map, the temperature around the geothermal prospect area is 22 – 25 0C. The results of the derivative analysis show that the geothermal prospect of Mount Hamiding is controlled by two different faults, a fault due to the depression of the old Hamiding caldera and a local fault under the surface of Mount Dukono, which is confirmed as a reverse fault. While the 2D modeling identified the geothermal reservoir layer, which is estimated to have a density of 1.59 gr/cc and consists of a mixture of tuff and minor lava, where the contents of this reservoir are water dominant due to the relatively low-density value with a depth of -411 – (-1280) m, above the reservoir layer it is suspected that the tuff and clay insert layer has a density of 2.56 gr/cc with a depth of 310 – (-1280) m, and the covering layer which is presumed to be a clay cap layer has a density of 1.39 gr/cc with a depth of 870 – (-620). ©2022 JNSMR UIN Walisongo. All rights reserved.